The Role of pknF and fbpA as a virulence genes with Interleukin-4and 6, in the Pathogenesis of Tuberculosis - Samih Riyadh Faisal - Zahrah Adnan Dakhel Alshammarii ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Tuberculosis (TB) is a global health problem caused by Mycobacterium tuberculosis (MTB), a bacterium that can evade the host immune system and keep at in a latent state. Drug-resistant strains of MTB, such as multi-drug resistant TB (MDR-TB), pose a significant challenge toward the TB control efforts. This study aimed to investigate the role of two MTB virulence genes, pknF and fbpA, and two host cytokines, Interleukin-4 and Interleukin-6, in the pathogenesis of TB. The expression levels of pknF and fbpA genes were measured by qPCR in (12) sensitive TB and (12) MDR-TB isolates. IL-4 and IL-6 were measured by ELISA in serum samples from (24) healthy controls, (12) patients having sensitive TB, and 12 patients having MDR-TB. The results revealed a significant difference in fbpA gene expression between MDR-TB (2.59± SE 0.36) and sensitive TB (1.01± SE0.037) isolates (P=0.0003), whereas pknF gene expression did not vary significantly across the two groups (2.53±0.62 in MDR-TB and 1.72±0.40 in sensitive TB) (p=0.289). IL-4 levels were markedly elevated in patients with MDR-TB (1091.967± SE 108.793 pg/ml) compared to the control group (105.3358 ± SE 5.543 pg/ml) (p<0.0001), but not significantly different from patients with sensitive TB (1054.763 ± SE 71.482 pg/ml). IL-6 levels were significantly higher in both MDR-TB and sensitive TB patients than in the control group (9.253 ± SE 0.456 pg/ml). However, MDR-TB patients showed a non-significant lower ratio of IL-6 (38.5851 ± Se 4.601 pg/ml) than sensitive TB patients (42.458 ± SE 1.809). A significant negative correlation were observed between fbpA gene expression and IL-4 levels in both MDR-TB and sensitive TB patients (r = -0.375; p < 0.0001 and r = -0.165; p < 0.0001, respectively), and a positive correlation between fbpA gene expression and IL-6 levels in both groups (r = 0.1006; p < 0.0001 and r = 0.466; p < 0.0001, respectively). These findings suggest that pknF and fbpA genes may play a role in the virulence of MTB, especially in drug-resistant strains, and that IL-4 and IL-6 may be involved in the host immune response to MTB infection. These potential biomarkers could be used to develop targeted therapies for MDR-TB and improve TB control efforts globally.